Leading Apple with Steve Jobs management lessons from a controversial genius - Elliot, Jay. (Laura Ann); 1906-1998. 1958- 1947- (Sandra M.); 1957- (Margaret M.) (Hoboken, New Jersey Wiley, 2012)
Jay Elliot, former Senior VP of Apple, shares how Steve Jobs motivated people to do the best work of their lives. Elliot was hired by Steve Jobs, just in time to accompany him on his last historic visit to Xerox's Palo Alto Research Center. Jay Elliot served as Steve's right-hand man and trouble-shooter, overseeing all corporate operations and business planning, as well as software development and human relations. In this book, he details how Steve managed and motivated his people. Steve Jobs used phrase "Pirates! Not the Navy" as a rallying cry, a metaphor to "Think Different." In developing the Macintosh, it became a four-word mission statement. Management principles that grew out of that statement form backbone of this book: How to find talented people who will understand your objectives and be able to make a contribution to that effort ; Lists traits that can determine whether a person will be so committed to the vision that they will provide their own motivation ; How to ensure that employees hold an allegiance to the captain and to his/her shipmates, and also possess the ability to come up with original, unique ways to approach a problem, and be self-guided with a strong sense of direction.
Includes bibliographical references and index.
Keywords: Jobs, Steve -- 1955-2011.; Computer industry -- United States; Industrial management; Computer industry; Industrial management